Nancy Clark's sports nutrition guidebook - Clark, Nancy, 1951- (Champaign, IL : Human Kinetics, 2014)
Provides nutritional advice for serious and casual athletes and includes recipes designed to boost health and fitness.
Everyday eating for active people. Building a high-energy eating plan ; Eating to stay healthy for the long run ; Breakfast : the key to a successful sports diet ; Lunch and dinner : at home, on the run, and on the road ; Between meals : snacking for health and sustained energy ; Carbohydrate : simplifying a complex topic ; Protein : building and repairing muscles ; Fluids : replacing sweat losses to maintain performance -- The science of eating and exercise. Fueling before exercise ; Fueling during and after exercise ; Supplements, performance enhancers, and engineered sports foods ; Nutrition and active women ; Athlete-specific nutrition advice -- Balancing weight and activity. Assessing your body : fat, fit, or fine? ; Gaining weight the healthy way ; Losing weight without starving ; Dieting gone awry : eating disorders and food obsessions -- Winning recipes for peak performance. Breads and breakfasts ; Pasta, potatoes, and rice ; Vegetables and salads ; Chicken and turkey ; Fish and seafood ; Beef and pork ; Beans and tofu ; Beverages and smoothies ; Snacks and desserts.
Includes bibliographical references (pages 481-497) and index.
Keywords: Athletes -- Nutrition